Enhancing mechanical properties of durian (Durio ziberthinus murr.) seed starch biopolymer filled with Indonesian bay leaf (Syzygium polyanthum) extract - Sunarsono, Hery; Abral, Hairul; Mahardika, Melbi; Muhammad Railis, Razan; Sapuan, S.M.; Azka, Muhammad Adlan; Rahmad, .; Arrafi, Muhammad Rizky (Elsevier, 2025)
The use of durian seed starch (DSS) for the production of biopolymers is a promising approach that contributes to sustainability. It utilizes a renewable and abundant resource that is often considered waste, turning it into a valuable product. Moreover, this approach helps reduce plastic waste and offers an eco-friendly alternative to petrochemical-based polymers, supporting efforts toward a more sustainable and circular economy. While there are challenges in terms of mechanical properties and processing, ongoing research and development continue to enhance the viability and performance of starch-based polymers. This study investigates the incorporation of Indonesian Bay Leaf extract (IBL) into DSS to become DSS/IBL biopolymer. Phytochemical analysis of IBL verified the existence of bioactive compounds like quercetin, a type of phenolic. This bioactive compound is very reactive, natural, and environmentally friendly, containing many hydroxyl groups (-OH), which are able to form complex bonds with other molecules and can interact with polymers. Thus, the presence of IBL led to enhanced mechanical properties of the biopolymer, improving tensile strength and modulus, 5.58 MPa and 0.27 GPa, respectively, for DSS/IBL1.2. The presence of quercetin of IBL in the DSS matrix has induced strong crosslinking within the DSS/IBL-biopolymer, effectively enhancing its structural integrity and forming a resistance mechanism against crack propagation. The resulting polymer holds promise as an improved mechanical property, a sustainable, and biodegradable alternative to petrochemical-based polymers, especially in bioplastics and eco-friendly packaging materials.